2014
DOI: 10.4311/2013mb0123
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate Effects on Number and Distribution of Fungi in the Włodarz Underground Complex in the Owl Mountains (Góry Sowie), Poland

Abstract: In July 2013 we studied the occurrence of fungi in an underground complex named Włodarz, located inside the massif of Włodarz, within the Owl Mountains, Lower Silesia, Poland. The study is the first mycological evaluation of the rocks in the Włodarz underground complex and the air inside and outside of it. To examine the air, the Air Ideal 3P sampler and PDA medium were used. Microbiological evaluation of the rocks inside the adit was performed using two methods, swab sampling and rinse sampling. The results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 21 publications
4
25
0
2
Order By: Relevance
“…Moreover, air samplers, such as the Air Ideal 3P sampler, are small in size, so they are useful for application in difficult conditions such as underground sites (Ogórek and Lejman, 2015). Ogórek et al (2014aOgórek et al ( , 2014bOgórek et al ( , 2014c and Pusz et al (2014Pusz et al ( , 2015, who studied fungi from air in underground sites, reported that higher levels of fungi were isolated from outside sites than from inside, as found in our study. Ecosystems such as underground sites, when compared to the external environment, are very unfavorable for survival and development of fungi due to the relatively stable low temperatures and very restricted availability of organic matter (Poulson and White, 1969;Barton and Northup, 2007).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Moreover, air samplers, such as the Air Ideal 3P sampler, are small in size, so they are useful for application in difficult conditions such as underground sites (Ogórek and Lejman, 2015). Ogórek et al (2014aOgórek et al ( , 2014bOgórek et al ( , 2014c and Pusz et al (2014Pusz et al ( , 2015, who studied fungi from air in underground sites, reported that higher levels of fungi were isolated from outside sites than from inside, as found in our study. Ecosystems such as underground sites, when compared to the external environment, are very unfavorable for survival and development of fungi due to the relatively stable low temperatures and very restricted availability of organic matter (Poulson and White, 1969;Barton and Northup, 2007).…”
Section: Discussionsupporting
confidence: 85%
“…As shown previously (Ogórek et al, 2014a(Ogórek et al, , 2014b(Ogórek et al, , 2014c, bioaerosols from the external environment most strongly influence the percentage composition of fungi in caves and other underground sites. Tourist activities are also very important, because they may have a serious impact on the hypogean system (Taylor et al, 2013).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…For example, in a Niedźwiedzia Cave in the Sudety moutain, which is often visited by tourists, Ogórek et al (2014a) reported the concentration of spores between 123 and 214 CFU/m 3 , while the most commonly isolated fungi were Cladosporium herbarium and Rhizopus stolonifer. Similar results were obtained by Ogórek et al (2014b) examining the air in an artificial underground complex named Włodarz, located inside the massif of Włodarz, within the Owl Mountains, Lower Silesia, Poland. Between 65.5 and 1003 colony-forming units of fungi per m 3 of air were isolated from the air sampled in the adit, and the most common fungus isolated from the air outside and inside the adit was Cladosporium cladosporioides, followed by C. herbarum at one location in the adit.…”
Section: Discussionsupporting
confidence: 78%
“…are common in many parts of the world, as they are cosmopolitan organisms. Their spores can be found in air, soil and water (Domsch et al, 1980;Ogórek et al, 2012). These fungi are active at low temperatures and in high air humidity (Kwon et al, 2001).…”
Section: Pusz Et Almentioning
confidence: 99%